Drosophila melanogaster as a High-Throughput Model for Host–Microbiota Interactions - Trinder, Mark; Daisley, Brendan A.; Dube, Josh S.; Reid, Gregor (Frontiers in Microbiology, 2017)
We agree no model is perfect and that D. melanogaster has its limitations like any other model. We would like to stress that we are not discrediting germ-free mouse models, but that researchers could benefit from supportive in vivo evidence (rather than in vitro) of their hypotheses before embarking down this expensive avenue. The cost and time-consuming nature of germ-free mouse studies requires strong conviction of hypotheses to warrant logical further investigation. The purpose of this perspective article is to bring attention to the under-considered areas of research that D. melanogaster may be a useful model for preliminary investigations. We highlight that the inexpensive and high-throughput D. melanogaster microbiota model can enable investigators to experiment with exploratory research questions such as probiotics, prebiotics, xenobiotics, and diet-genetic interactions before verification in costlier models. D. melanogaster microbiota simplicity also enables researchers to develop predictive models of how polymicrobial interactions affect host physiology before testing in more complex hosts (a common theme in biological animal models which you have alluded to previously). Altogether, we agree that there are limitations to the D. melanogaster model. We have now explicitly pointed out the major shortcomings of this model in the Future Directions and Conclusions section and made reference to review articles addressing these limitations in more detail. We hope this will better inform readers while also abiding to the strict space limitations inherent of perspective articles.